Potential environmental risks of nanopesticides: Application of Cu(OH)2 nanopesticides to soil mitigates the degradation of neonicotinoid thiacloprid. (August 2019) - Zhang, Xiaoxia; Xu, Zhenlan; Wu, Mansha; Qian, Xiaoting; Lin, Daohui; Zhang, Hangjun; Tang, Juan; Zeng, Tao; Yao, Weijun; Filser, Juliane; Li, Lingxiangyu; Sharma, Virender K.
Abstract: Cu(OH)2 nanopesticides and organic insecticides are continuously applied to soil at a temporal interval, while knowledge about the impact of Cu(OH)2 nanopesticides on organic insecticides degradation is currently scarce, resulting in poorly comprehensive evaluation of the potential environmental risks of Cu(OH)2 nanopesticides. Herein, a commercial Cu(OH)2 nanopesticide formulation (NPF), the active ingredient of NPF (AI-NPF), the prepared Cu(OH)2 nanotubes (NT) with comparable morphology and size to AI-NPF, and CuSO4 were respectively applied to soil at normal doses (0.5, 5 and 50 mg/kg), followed by an application of neonicotinoid thiacloprid after an interval of 21 d, showing that NPF at doses of 5 and 50 mg/kg significantly ( p  < 0.05) mitigated thiacloprid degradation compared to control and CuSO4 . Furthermore, AI-NPF was the primary component that contributed to the mitigation effect of NPF, which was also validated by the NT. Large differences in the degradation efficiency of thiacloprid in sterilized and unsterilized soils with Cu(OH)2 nanopesticides suggested that biodegradation was the primary process responsible for thiacloprid degradation, especially as chemical degradation was negligible. Besides a decrease of thiacloprid bioavailability due to adsorption by Cu(OH)2 nanopesticides, we demonstrated that Cu(OH)2 nanopesticides changed soil microbial communities, reduced nitrile hydratase activity and down-regulated thiacloprid-degradative nth gene abundance, which thus mitigated thiacloprid biodegradation. Clearly, this study shed light on the potential environmental risks of Cu(OH)2 nanopesticide. Graphical abstract: Unlabelled Image Highlights: Cu(OH)2 nanopesticides at normal doses mitigated degradation of thiacloprid in soil. Compared to CuSO4, Cu(OH)2 nanopesticides showed strong mitigation effects. Bioavailability of thiacloprid decreased due to adsorption by Cu(OH)2 nanopesticides. Application of Cu(OH)2 nanopesticides to soil would change microbial communities. Cu(OH)2 nanopesticides down-regulated thiacloprid-degradative nth gene abundance.